Epidemiology of the Viral Hepatitis-HIV Syndemic in San Francisco: A Collaborative Surveillance Approach. (January 2014) - Sanchez, Melissa A.; Scheer, Susan; Shallow, Sue; Pipkin, Sharon; Huang, Sandra
Objectives: To describe the epidemiology of people coinfected with hepatitis B virus (HBV) or hepatitis C virus (HCV) and HIV in San Francisco, the San Francisco Department of Public Health's Communicable Disease Control and Prevention Section and the HIV Epidemiology Section collaborated to link their registries. Methods: In San Francisco, hepatitis reporting is primarily through passive laboratory-based surveillance, and HIV/AIDS reporting is primarily through laboratory-initiated active surveillance. We conducted the registry linkage in 2010 using a sequential algorithm. Results: The registry match included 31, 997 HBV-infected people who were reported starting in 1984; 10, 121 HCV-infected people who were reported starting in 2001; and 34, 551 HIV/AIDS cases reported beginning in 1981. Of the HBV and HCV cases, 6.3% and 12.6% were coinfected with HIV, respectively. The majority of cases were white males; however, black people were disproportionately affected. For more than 90% of the HBV/HIV cases, male-to-male sexual contact (men who have sex with men [MSM]) was the risk factor for HIV infection. Injection drug use was the most frequent risk factor for HIV infection among the HCV/HIV cases; however, 35.6% of the HCV/HIV coinfected males were MSM but not injection drug users. Conclusions: By linking the two registries, we found new ways to foster collaborative work and expand our programmatic flexibility. This analysis identified particular populations at risk for coinfection, which can be used by viral hepatitis and HIV screening, prevention, and treatment programs to integrate, enhance, target, and prioritize prevention services and clinical care within the community to maximize health outcomes.